CADRE EMPOWERMENT PROGRAM FOR HYPERTENSION PREVENTION IN VILLAGE JUBEL, BANTUR VILLAGE, BANTUR DISTRICT - Sena Purwanza; Yuyud Wahyudi (Indonesian Journal of Community Health Nursing, 2022)
Introduction: hypertension is the highest degenerative disease in Malang Regency and the second rank in East Java Province. One effort that is sufficient is to apply the Health Belief Model to predict and explain variations in healthy living behavior. This study aims to determine the effectiveness of the cadre empowerment intervention program in preventing hypertension. Methods: This research was conducted in January - February 2022 using a quasi-experimental research design using a two-group pretest-posttest design with a control group design with a sample of 12 cadres with a total sampling technique. Results: The results of this study indicate that the cadre empowerment program before the intervention (pre-test) was mostly adequate, after the intervention (post-test) most of the behavior was sufficient. Conclusion: the cadre empowerment program showed effective test results because there was an increase from before and after the intervention. Keywords: cadre empowerment intervention; hypertension; prevention